Effective kinetic description of the expanding overoccupied glasma - Tanji, Naoto; Venugopalan, Raju (Physical review, 2017)
We report on a numerical study of the Boltzmann equation including 2↔2 scatterings of gluons and quarks in an overoccupied glasma undergoing longitudinal expansion. We find that when a cascade of gluon number to the infrared occurs, corresponding to an infrared enhancement analogous to a transient Bose-Einstein condensate, gluon distributions qualitatively reproduce the results of classical-statistical simulations for the expanding glasma. These include key features of the distributions that are not anticipated in the “bottom-up” thermalization scenario. We also find that quark distributions, like those of gluons, satisfy self-similar scaling distributions in the overoccupied glasma. We discuss the implications of these results for a deeper understanding of the self-similarity and universality of parton distributions in the glasma.